Análisis de los niveles de educación existentes en la parroquia urbana Siete de Octubre y su incidencia en el índice de subempleo de las familias del sector, durante el año 2012 - Valencia Cabrera, Gabriela Patricia (2013)
This thesis entitled "Analysis of existing education levels in the Urban Parish October Seven and its impact on the underemployment rate of families in the industry, in 2012" had the primary actors to household heads of major streets of the parish of the same name. The objectives of this thesis were: analysis of existing education levels in the Urban Parish October Seven and its impact on the underemployment rate of families in the sector during the year 2012, research the type of work they do heads of household, the income received and the percentage allocated to cover basic needs, establish underemployment rates of families in the parish and identify the consequences of underemployment in the quality of education of the inhabitants of the Parish Urbana Seven October. We used three research methods; inductive, deductive, analytical; also applied two types of research, applied and descriptive; also used a survey form as a technique for gathering information, the same that was provided by household heads Seven Urban Parish of October. From research the following information was obtained: 35% of household heads surveyed Urban Parish October Seven, achieved through high school, 22.8% reached primary, 17.4% third level, while which 8.4% have not achieved any academic level. According to 33.8% of household heads surveyed, at least one member per family are studying in primary, secondary 35.6%, 16.2% third level and fourth level of 1.8%. Regarding their occupation, 39.8% of household heads working in the area of services such as, auto mechanics, electricians, maids, clerks, soldiers, policemen, teachers, journalists, doctors, lawyers, truck drivers, etc.., The 33.2% work in the commercial area expending all kinds of perishable and non-perishable, 11.4% are engaged in the agricultural sector as owners, xxiii managers, employees, laborers and laborers both short and perennial cycle, the 12.6% are active for the industrial and, construction and manufacturing, so that the 0.3% work in the financial sector. 28.7% of household heads monthly incomes between $ 251 and $ 350, while for 18.3% their pay is between $ 351 and $ 450, 5.7% of household heads derive income only from $ 50 to $ 150, why not cover the basic food basket. Most of the household heads use 50% to meet the basic needs of food, 20% invest in education, 10% for health, housing, clothing and under other 20%. The underemployment rate in the inhabitants of the Parish Urbana Seven October is 29.04%, whereas the invisible is 6.59%, so that the total underemployment is 55.35%, data demonstrating that the underemployment rate is the dominant sector in families. The 11% of household heads said that the main reason why we do not have jobs is because they have stable professional degree, 10% think it's for lack of work, 3.6% sales and incomes of their business, 2.4% by lack of capital and 1.8% of old age and health. The research sector families allowed to know, that underemployment from having a good quality of education, making it impossible to achieve a better standard and quality of life, so it is important that the general public constantly prepare and generate authorities employment sources to meet the needs, also preventing further exploiting natural resources and exploit the intellectual resources.